2008
DOI: 10.1007/s11661-008-9506-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Embrittlement Mechanism in Fatigue of Austenitic Stainless Steels

Abstract: YUKITAKA MURAKAMI, TOSHIHIKO KANEZAKI, YOJI MINE, and SABURO MATSUOKAThe basic mechanism of the hydrogen embrittlement (HE) of stainless steels under fatigue loading is revealed as microscopic ductile fracture, resulting from hydrogen concentration at crack tips leading to hydrogen-enhanced slip. Fatigue crack growth rates in the presence of hydrogen are strongly frequency dependent. Nondiffusible hydrogen, at a level of 2 to approximately 3 wppm, is contained in ordinarily heat-treated austenitic stainless st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(114 citation statements)
references
References 48 publications
6
94
0
Order By: Relevance
“…It is reported that hydrogen enhances fatigue crack initiation and propagation in tension-compression fatigue 26) , rotating bending fatigue 25) and torsion fatigue 27) . They suggested that these phenomena are due to the localization of plasticity at the fatigue crack tip caused by hydrogen.…”
Section: Results On Rolling Contact Fatigue Tests Under Contaminated mentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that hydrogen enhances fatigue crack initiation and propagation in tension-compression fatigue 26) , rotating bending fatigue 25) and torsion fatigue 27) . They suggested that these phenomena are due to the localization of plasticity at the fatigue crack tip caused by hydrogen.…”
Section: Results On Rolling Contact Fatigue Tests Under Contaminated mentioning
confidence: 99%
“…It has been reported in studies about delayed fracture [6][7][8] and tension-compression fatigue fracture 25,26) that hydrogen localizes plasticity. Therefore, it is presumed that the basic role of hydrogen in the rolling contact fatigue process is the same as in the case of both the delayed fracture and the tension-compression fatigue fracture.…”
Section: Rolling Contact Fatigue Testing Under Contaminated Lubricatimentioning
confidence: 99%
“…Along with degradation of basic mechanical properties, hydrogen significantly reduces fatigue lifetime of stainless steels, and even insignificant content of residual hydrogen in materials (about 2-3 weight ppm) can markedly increase fatigue crack growth rate as it was shown by Murakami et al [8]. The effect of hydrogen was markedly enhanced at low frequencies of loading [8], evidently due to ability of hydrogen clouds accompany dislocations during dislocation slip and due to a difference in densities of H clouds around the dislocations at high and low frequencies. The influence of hydrogen on the fatigue properties of stainless steels attracts particular attention, with a view to prolonging service lifetime of items working in high-pressure hydrogen environments.…”
Section: Introductionmentioning
confidence: 86%
“…iron-based alloys subjected to cathodic hydrogen charging (see, e.g., [9]). Taking into account the results obtained by Murakami et al [8] at low frequencies, there is a need of measuring internal friction of stainless steels under forced sub-resonant vibrations. Usually, internal friction studies of hydrogen charged steels come to measurements of temperature-or amplitude-dependent internal friction (IF) at frequencies that are rarely less than 0.5 Hz due to specimen shapes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, diffusible hydrogen can freely move, and easily accumulates to form hydrogen molecules which damage the host material. Some reports have indicated that hydrogen atoms within a material can be released by long-duration baking, reducing HE susceptibility [8,9]. Hwang et al reported that adding particular elements to low-carbon steel can enhance the hardenability of steel [10].…”
Section: Introductionmentioning
confidence: 99%